Molecular footprints reveal the impact of the protective HLA-A*03 allele in hepatitis C virus infection. Issue 11 (6th May 2011) - Fitzmaurice, Karen; Petrovic, Danijela; Ramamurthy, Narayan; Simmons, Ruth; Merani, Shazma; Gaudieri, Silvana; Sims, Stuart; Dempsey, Eugene; Freitas, Elizabeth; Lea, Susan; McKiernan, Susan; Norris, Suzanne; et al.
Abstract : Background and aims: CD8 T cells are central to the control of hepatitis C virus (HCV) although the key features of a successful CD8 T cell response remain to be defined. In a cohort of Irish women infected by a single source, a strong association between viral clearance and the human lecucocyte (HLA)-A*03 allele has been described, and the aim of this study was to define the protective nature of the associated CD8 T cell response. Methods: A sequence-led approach was used to identify HLA-A*03-restricted epitopes. We examine the CD8 T cell response associated with this gene and address the likely mechanism underpinning this protective effect in this special cohort, using viral sequencing, T cell assays and analysis of fitness of viral mutants. Results: A strong 'HLA footprint' in a novel NS3 epitope (TVYHGAGTK) was observed. A lysine (K) to arginine (R) substitution at position 9 (K1088R) was seen in a significant number of A*03-positive patients (9/12) compared with the control group (1/33, p=0.0003). Threonine (T) was also substituted with alanine (A) at position 8 (T1087A) more frequently in A*03-positive patients (6/12) compared with controls (2/33, p=0.01), and the double substitution of TK to AR was also observed predominantly in HLA-A*03-positive patients (p=0.004). Epitope-specific CD8 T cell responses were observed in 60% of patients three decades after exposure and the mutants selected in vivo impacted on recognition in vitro. Using HCV replicons matched to the viral sequences, viral fitness was found to be markedly reduced by the K1088R substitution but restored by the second substitution T1087A. Conclusions: It is proposed that at least part of the protective effect of HLA-A*03 results from targeting of this key epitope in a functional site: the requirement for two mutations to balance fitness and escape provides an initial host advantage. This study highlights the potential protective impact of common HLA-A alleles against persistent viruses, with important implications for HCV vaccine studies.